2006
DOI: 10.1364/opex.14.000817
|View full text |Cite
|
Sign up to set email alerts
|

Self-induced optical modulation of the transmission through a high-Q silicon microdisk resonator

Abstract: Direct time-domain observations are reported of a low-power, self-induced modulation of the transmitted optical power through a high-Q silicon microdisk resonator. Above a threshold input power of 60 µW the transmission versus wavelength deviates from a simple optical bistability behavior, and the transmission intensity becomes highly oscillatory in nature. The transmission oscillations are seen to consist of a train of sharp transmission dips of width approximately 100 ns and period close to 1 µs. A model of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
193
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 222 publications
(202 citation statements)
references
References 34 publications
8
193
1
Order By: Relevance
“…[16][17][18][19] Studies have shown abundant nonlinear behaviors promoted by the highly localized optical field inside the microcavities, such as optical bi-stability, 20,21 deformation and abnormal oscillation [22][23][24][25][26][27] of the transmission spectra. Recently, periodic self-sustained pulsation (SSP) [28][29][30][31][32] in the transmission spectrum has been reported in various microcavity systems, excited by a fixed-frequency continuous laser, different from that excited by frequency-scanned lasers 26 or by pulsed lasers 27 in previous studies.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18][19] Studies have shown abundant nonlinear behaviors promoted by the highly localized optical field inside the microcavities, such as optical bi-stability, 20,21 deformation and abnormal oscillation [22][23][24][25][26][27] of the transmission spectra. Recently, periodic self-sustained pulsation (SSP) [28][29][30][31][32] in the transmission spectrum has been reported in various microcavity systems, excited by a fixed-frequency continuous laser, different from that excited by frequency-scanned lasers 26 or by pulsed lasers 27 in previous studies.…”
Section: Introductionmentioning
confidence: 99%
“…As such, we combine the arguably best material for high-QM nanomechanics [20] (stoichiometric Si3N4) with an advantageous material for linear optics [21][22][23][24] (SiO2) in an integrated on-chip device, which allows the detection of ultra-small forces at the aN level. The advantages of silica for optical resonators result from higher thresholds for thermal nonlinearities when compared to silicon [25] or silicon nitride [26] as well as the absence of two photon absorption [27], thus allowing significantly higher circulating power and preventing cross talk between optical modes induced by the nonlinearity. Moreover, silica microresonators can be coupled with high efficiency to optical fiber as required for highly efficient measurements of position or force.…”
mentioning
confidence: 99%
“…21 However, due to the ultrahigh Q of the CaF 2 WGM microcavity, these thermal effects become apparent even when the temperature change is small. When the resonance wavelength of the cold microcavity is λ 0 , the resonant 2016) wavelength λ r (t) of the microcavity system is given as [8][9][10][11][12][13] λ r (t) = λ 0…”
Section: A Master Rate Equationsmentioning
confidence: 99%
“…This effect is called thermo-opto-mechanical (TOM) oscillation. [8][9][10][11][12][13] In this paper, we first describe the fabrication of a CaF 2 WGM microcavity with computer controlled ultra-precision cutting. This process enables us to control the diameter and study the size dependence of WGM microcavities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation